Recyclable 0D/2D ZnFe2O4/Bi5FeTi3O15 S-scheme heterojunction with bismuth decoration for enhanced visible-light-driven tetracycline photodegradation. Issue 12 (15th June 2021) - Zhang, Ke; Li, Danqing; Tian, Qingyun; Cao, Hongyang; Orudzhev, Farid; Zvereva, Irina A.; Xu, Jingkun; Wang, Chuanyi
Abstract: Practical application of photocatalysis is often challenged by some intrinsic issues such as recombination of photogenerated charge carriers, stability and separation, etc. Herein, bismuth decorated 0D/2D ZnFe2 O4 /Bi5 FeTi3 O15 (Bi/ZF/BFT) step-scheme (S-scheme) heterojunction was fabricated by an in-situ method. Due to the advantages of structure and composition, the Bi/ZF/BFT with the desired proportion (Bi/ZF/BFT-35) exhibits favorable photocatalytic performance towards tetracycline (TC) degradation. Compared with the pure ZF, the nanohybrid shows superior stability after 5 times cycle tests. Moreover, Bi/ZF/BFT-35 is convenient to be separated from the reaction system due to its magnetic nature. As identified by ESR measurement, O2 − and OH radicals were involved in the photodegradation of TC, which supports that the S-scheme is successfully prepared. Also, the Bi/ZF/BFT-35 shows great ability of chemical oxygen demand (COD) removal in the practical wastewater as well. Importantly, antibacterial activity against E. coli test indicates that photodegraded TC has lower biotoxicity. The present work demonstrates that cocatalyst Bi modified ZF/BFT S-scheme can not only significantly improve its stability with good recyclability from the reaction system, but also inhibits the recombination of charge carriers, giving insight on the strategy of fabricating a promising photocatalyst for practical wastewater treatment.